ANALISIS PENGARUH KINERJA LOGISTIK PEMASOK TERHADAP KINERJA BISNIS (Studi Pada Bengkel AHASS di Kota Semarang) - Haryotejo, Bimo; Kusumawardhani, Amie (Diponegoro Journal of Management, 2015)
Logistics so far  is the science which should be able to special attention. Because good logistics  will support a business performance of the effectiveness and efficiency. This study aims to analyze the influence of suppliers logistics performance to business performance, case studies at AHASS workshop in Semarang. Suppliers Logistics performance in this research represented by transportation , distribution center location , and inventory variable.  the results of the analysis shows that the transportation and inventory have a positive and significant influence to business performance.While the distribution center location  have not  significant influence to business performance.